2018
DOI: 10.11591/eei.v7i3.687
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Implementation of Mean, Variance and Skewness Statistic Formula for Image Processing Using FPGA Device

Abstract: Processing statistic formula in image processing and accessing data from memory is easy in software, the other hand for hardware implementation is more dificult considering a lot of constraint. This article proposes an implementation of optimum mean, variance and skewness formula in FGPA Device. The proposed circuit design for all formulas only need three additions component (in three accumulators) and two divisions using two shift-right-registers, two subtractors, one adder and six multipliers. For 8x8 image … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…Tables 4 and 5 present the matrix of correlation coefficients and statistical characteristics of the RSSI data measured in Quito and Valle de los Chillos after having applied the inverse normal distribution method dividing the data with the LQI. It can be observed that the statistical characteristics in each LQI range are very small, with which the accuracy of the inverse normal distribution algorithm can be evidenced, the value that changes the most in relation to the original data is the variance, which represents the variability of a data series with respect to its mean [33]. A small decrease in the dispersion of the data found with respect to its mean is denoted, this effect was more evident in the "GOOD" range, decreasing the variance by 12.77%.…”
Section: Resultsmentioning
confidence: 99%
“…Tables 4 and 5 present the matrix of correlation coefficients and statistical characteristics of the RSSI data measured in Quito and Valle de los Chillos after having applied the inverse normal distribution method dividing the data with the LQI. It can be observed that the statistical characteristics in each LQI range are very small, with which the accuracy of the inverse normal distribution algorithm can be evidenced, the value that changes the most in relation to the original data is the variance, which represents the variability of a data series with respect to its mean [33]. A small decrease in the dispersion of the data found with respect to its mean is denoted, this effect was more evident in the "GOOD" range, decreasing the variance by 12.77%.…”
Section: Resultsmentioning
confidence: 99%
“…Descriptive statistics, which includes Mean, Max value, Min value, Quartile or Q values-Q1, 2 or Median, and 3, Standard deviation is the most basic but highly informative statistical data mining technique to obtain enough light on the nature and distribution of any data [30]. Another important parameter is the 'Skewness' of the data [31]. It is an estimation of data distribution and its direction.…”
Section: Feature Extractionmentioning
confidence: 99%
“…the local minima or maxima of first derivative are utilized to detect the points lying on an edge as illustrated in Figure 2 [8], [16].…”
Section: First Order Edge Detectionmentioning
confidence: 99%